Study of ultrashort laser-pulse induced ripples formed at the interface of silicon-dioxide on silicon - Liu, Bing (My University, 2013)
In this thesis, the ripple formation at the interface of SiO2 and Si were studied in a systematic fashion by irradiating the SiO2-Si samples with ultrashort laser pulses under a broad variety of experimental conditions. They consist of di↵erent irradiating laser wavelengths, incident laser energies, translation speeds, translation directions, spot sizes of the laser beam, as well as oxide thicknesses. The ripples produced by laser irradiation are examined using various microscopy techniques in order to characterize their surface morphology, detailed structures, crystalline properties, and so on. For the experiments carried out at ! = 800 nm, the ripples formed on the SiO2-Si sample with an oxide thickness of 216 nm were first observed under optical microscopy and SEM. After removing the oxide layer with HF solution, the surface features of the ripples on the Si substrate were investigated using SEM and AFM techniques. Subsequently, by means of TEM and EDX analysis, the material composition and crystallinity of the ripples were determined. It is concluded that the ripples are composed of nano-crystalline silicon. In addition to the 216 nm oxide thickness, other oxide samples with di↵erent oxide thicknesses, such as 24, 112, 117, 158 and 1013 nm, were also processed under laser irradiation. The ripple formation as a function of the laser energy, the translation direction and the spot size is discussed in detail. Furthermore, the ripples created at the SiO2-Si interface are compared with
the LIPSS created on pure silicon samples that were processed under similar laser irradiation conditions. The spatial periodicities of the ripples were evaluated to be in the range of between 510 nm and 700 nm, which vary with the oxide thickness and other laser parameters. For the experiments using the ! = 400 nm laser pulses, it is found that ripples can also be formed at the SiO2-Si interface, which have spatial periodicities in the range of between 310 nm and 350 nm depending on the oxide thickness. The ripple formation at this 400 nm wavelength as a function of the laser energy, the translation speed, and translation direction is considered as well. For the case of ! = 400 nm irradiation, a comparison is also made between the interface ripples on the SiO2-Si samples and the LIPSS on a pure Si sample. Through FIB-TEM and EDX analysis, it confirmed that the ripples were produced in the substrate while the oxide layer maintained its structural integrity. In addition, the ripples are composed of nano-crystalline silicon whose crystallite sizes are on the order of a few nanometers. Apart from irradiating oxide samples with femtosecond laser pulses, which applies to the two cases of ! = 800 and 400 nm mentioned above, oxide samples with an oxide thickness of 112 nm were irradiated with picosecond laser pulses at ! = 800 nm whose pulse durations are 1 ps and 5 ps, respectively. However, no regular ripples can be produced at the SiO2-Si interface while maintaining the complete integrity of the oxide layer.
Keywords: ripples; ultrashort laser-pulse; LIPSS; interface; oxide; Atomic, Molecular and Optical Physics; Biological and Chemical Physics; Engineering Physics; Nanoscience and Nanotechnology; Optics; Plasma and Beam Physics; Atomic, Molecular and Optical Physics